Perancangan Sistem Web Inventori Dan Produksi Menggunakan Metode Agile PT Intect Teknologi - Putra, Dhamar; Nanang, (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
Manufacturers that rely on manual record-keeping and external third-party platforms commonly experience data inaccuracy, slow coordination, and weak traceability of component stock. This study designs and builds an independent web-based inventory and production management system for PT InTect Teknologi Indonesia, a projector manufacturer, to address those limitations. The application, named SCMS InTect, was developed using the Agile (iterative) approach so that its features could grow incrementally in line with internal requirements. It was implemented with the Laravel framework on the back end and Vue.js on the front end, and is built around Bill of Materials (BOM) management, dual-state stock tracking (available and reserved), and a tiered approval workflow spanning Staff, Manager, and Director. Functional validation through black-box testing across six modules—authentication, master data, purchase order, assembly, sales order, and after-sales service—returned a fully successful outcome, confirming that automatic stock mutation behaves correctly during goods receipt, assembly completion, delivery, and servicing. The results indicate that the system removes the company’s dependence on the external LabShare platform, lowers manual recording errors, and improves the accuracy and timeliness of inventory data. The work offers a practical reference for integrating production and inventory control in small manufacturers through agile, framework-based web development.